Pengukuran Indeks Desa Zakat dalam Mendukung Program Zakat Community Development (Studi pada Desa Terantang Kabupaten Barito Kuala) - Rahmadinda, Alifya Sabila; Budiman, Mochammad Arif (P3M Politeknik Negeri Banjarmasin, 2024)
This study aims to explain the results of measuring the Zakat Village Index (Indeks Desa Zakat, IDZ) in supporting the Zakat Community Development (ZCD) program in Terantang Village, Mandastana District, Barito Kuala Regency. This research adopts a mixed-methods approach, combining qualitative and quantitative methods. The data sources used include primary data collected through interviews and Focus Group Discussions (FGDs) as well as secondary data in the form of Village Potential Data (PODES) documentation. The analytical tool employed is the Zakat Village Index (IDZ), developed by the Strategic Studies Center of the National Amil Zakat Agency (Puskas BAZNAS), using the Multi-Stage Weighted Index calculation method. The findings reveal that the Zakat Village Index (IDZ) measurement for Terantang Village yielded a total index score of 0.58. This score indicates that the overall condition of Terantang Village falls into the